An Extension of the Theory of Planned Behavior: the Role of Environmental and Economic Benefit in Shaping Purchase Intentions of Electric Motorcycles in West Java - Eka Septiarini; Tania Adialita; Sarah Febrina Yolanda (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The transportation sector is a major contributor to carbon emissions, and the adoption of electric motorcycles could offer a solution for sustainable mobility in Indonesia. However, despite government incentives and increasing environmental awareness, purchase intention for electric motorcycles remains low, particularly in West Java.Purpose: Although the Theory of Planned Behavior (TPB) is widely applied to explain pro-environmental behavior, limited studies have integrated perceived environmental and economic benefit, as well as perceived incentive policies, into the model. This study addresses the gap by extending TPB to examine their roles in shaping purchase intentions for electric motorcycles, particularly in West Java.Methodology: This study employs a cross-sectional survey using convenience sampling of 222 respondents in West Java, a relevant context and emerging market for electric motorcycles. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and mediating effects, although the non-probability sampling approach may limit generalizability. Findings: The results indicate that perceived environmental and economic benefits are the strongest predictors of purchase intention, with attitude playing a key mediating role. In contrast, incentive policies show a more limited effect, highlighting that consumers are more driven by perceived value than external policy support. In addition, the model explains 70.2% of the variance in purchase intention, indicating strong predictive relevance.Conclusion: The study contributes to the literature by extending the TPB to incorporate perceived benefits and policy incentives in the context of electric motorcycle adoption. From a managerial perspective in Indonesia, the findings suggest the importance of emphasizing concrete environmental and economic value propositions, as consumer decisions appear to be driven more by perceived benefits than by external policy support.Originality/Value: This study extends the Theory of Planned Behavior (TPB) by integrating environmental, economic, and policy perception variables in the context of electric motorcycle adoption in a developing country. The findings provide empirical evidence and practical insights for policymakers and marketers to design effective strategies that bridge the gap between positive perceptions and actual purchasing behavior. Keywords: perceived environmental benefit, perceived economic benefit, attitude, purchase intention, electric motorcycles